2016
DOI: 10.5539/enrr.v6n2p1
|View full text |Cite
|
Sign up to set email alerts
|

Community Participation in Decentralized Management of Natural Resources in the Southern Region of Mali

Abstract: Key messages Decentralized governance of natural resources is considered one of the key strategies for promoting sustainable management of natural resources at local level.  Local institutions governing natural resource management can serve as viable policy instruments to promote equitable and sustainable use of natural resources, and reduce conflict if strengthened through appropriate and inclusive processes involving the local communities and the State agencies.  Strengthening local conventions management… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…The existing local institutions are sometimes behind in addressing the dynamics of natural resource use in response to demographic pressure and new economic interest. Umutoni et al (2016a) found that the natural resource institutions in southern Mali are weak, as the majority of them are oral and the participation of the community members in their elaboration was low. Thus, this raises the need for the communities to reinforce local institutions which regulate access to natural resources and use by various actors.…”
Section: Discussionmentioning
confidence: 99%
“…The existing local institutions are sometimes behind in addressing the dynamics of natural resource use in response to demographic pressure and new economic interest. Umutoni et al (2016a) found that the natural resource institutions in southern Mali are weak, as the majority of them are oral and the participation of the community members in their elaboration was low. Thus, this raises the need for the communities to reinforce local institutions which regulate access to natural resources and use by various actors.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, privatisation of rangeland tenures in Botswana and Kenya led to the loss of communal grazing lands and actually increased rangeland degradation (Basupi et al 2017;Kihiu 2016) as pastoralists needed to graze livestock on now smaller communal pastures. Since food insecurity in drylands is strongly affected by climate risks, there is robust evidence and high agreement that resilience to climate risks is higher with flexible tenure for allowing mobility for pastoralist communities, and not fragmenting their areas of movement (Behnke 1994;Holden and Ghebru 2016;Liao et al 2017;Turner et al 2016;Wario et al 2016). More research is needed on the optimal tenure mix, including low-cost land certification, redistribution reforms, market-assisted reforms and gender-responsive reforms, as well as collective forms of land tenure such as communal land tenure and cooperative land tenure (see Section 7.6.5 for a broader discussion of land tenure security under climate change).…”
Section: Education and Expanding Access To Agricultural Servicesmentioning
confidence: 99%
“…The success of decentralised natural resource management initiatives depends on increased participation and empowerment of a diverse set of community members, not only local leaders and elites, in the design and management of local resource management institutions (Kadirbeyoglu and Özertan 2015;Umutoni et al 2016), while considering the interactions between actors and institutions at different levels of governance (Andersson and Ostrom 2008;Carlisle and Gruby 2017;McCord et al 2017). An example of such programmes where local communities played a major role in land restoration and rehabilitation activities is the cooperative project on The National Afforestation and Erosion Control Mobilization Action Plan in Turkey, initiated by the Turkish Ministry of Agriculture and Forestry (Çalişkan and Boydak 2017), with the investment of 1.8 billion USD between 2008 and 2012.…”
Section: Education and Expanding Access To Agricultural Servicesmentioning
confidence: 99%
“…Umutoni and Ayantunde (2018) [13] argued that the existing local institutions are sometimes slow in addressing the dynamics of natural resource use in response to demographic pressure and new economic interest. As reported by [14] in the case of southern Mali, natural resource governance is weak, as the majority of regulations/laws are oral, and the participation of the community members in their elaboration is very low. To prevent recurrent cycles of violent conflicts between transhumant herders and farmers, the parliament of Benin revised the national pastoral code in July 2018, which ignores the interests of various community actors and their perceived effects of transhumance on natural resource conservation.…”
Section: Introductionmentioning
confidence: 99%